LARGE SULFIDE-QUARTZ STOCKWORK GOLD DEPOSITS OF KAZAKHSTAN – FORMATION CONDITIONS AND PREDICTING CRITERIA - Mizernaya, M.; Dyackov, B.; Miroshnikova, A.; Mizerny, A.; Orazbekova, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The objective of the present study is to identify gold mineralization and associated elements distribution patterns in gold-bearing stockworks of gold-sulphide-quartz type large deposits in Northern and Eastern Kazakhstan and to detect geological and structural position of x-ore stockworks. Main methods are field studies within the Vasilkovskoye ore field in northern Kazakhstan and the Sekisovskoye ore field in eastern Kazakhstan. Samples of ore-bearing magmatic rocks and ore bodies were taken to determine the chemical composition and distribution patterns of the main ore minerals and impurities. Microprobe analysis using a scanning electron JSM 6390LV microscope with an energy-dispersive attachment, comparative characteristics of ore mineralization in the fields studied was made. Results of the study of the completed research and comparative analysis of data from other regions of the world show that large stockwork gold-sulphide-quartz with tellurides and bismuth-bearing Vasilkovskoye and Sekisovskoye ore deposits formed in a period of high tectonic activity in the earth's crust within regional geologic collision type structures, in the process of rhythmically pulsating displacement and tuck in the lithospheric plates and blocks.The position of ore stockworks is controlled by crust-magnesium deep splits, thrust structures and hypabyssal  intrusions of gabbro-diorite-granodiorite-plagiogranite series. The mineralization is associated with intense tectonic crushing processes and hydrothermal-metasomatic transformation of host rocks, manifested in microclinization, albitization, propylitic alteration, beresitization and silicification as well as injection of ore minerals. The ore bodies are characterized by Au-Ag-Bi-Te specialization. The gold is of two types: free and banded with sulfides, the mineralization vertical distribution range being significant (more than 500–800 m). The banded gold deposits in the Vasilkovskoye are localized in arsenopyrites, in the Sekisovskoye deposit gold mineralization is banded with pyrites of several generations. Scientific novelty is that complex compounds of silver and gold with tellurium have been revealed in the Sekisovskoye and, with tellurium and bismuth in ores of the Vasilkovskoye deposit. The complexity of ores involves setting a versatile task of basic and trace elements recording during all stages of work: from geological evaluation to production exploration. Modern processing technology and the latest development techniques allow classifying those fields as objects of industrial development priority. Studying them has scientific significance in the matter of endogenous ore formation, and creates a prerequisite to identifying promising new areas and deposits, both in Kazakhstan and in other parts of the world.
Keywords: gold deposit; intrusion; stockwork; tellurides; bismuth; Kazakhstan